2015
DOI: 10.1097/eja.0000000000000052
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anxiety-like behaviour in a rat model of acute postoperative pain

Abstract: We report that a rat model of acute postoperative pain is associated with anxiety-like increased light and open arm avoidance behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
0
12
1
Order By: Relevance
“…More recently, anxiety- and depression-like behaviors were investigated after plantar incision; for example, rats show an increase in anxiety-like avoidance behaviors in the light/dark box and an increase in depression-like behavior (sucrose preference test) for some days after incision. 86 , 168 Other studies assessing anxiety-like behavior after incision in rats gave similar results by using slightly different approaches and study designs. 36 , 97 Interestingly, the anxiety-like behavior lasted longer than hyperalgesia in 2 (but not one) of these studies.…”
Section: Animal-experimental Basic Researchmentioning
confidence: 89%
See 1 more Smart Citation
“…More recently, anxiety- and depression-like behaviors were investigated after plantar incision; for example, rats show an increase in anxiety-like avoidance behaviors in the light/dark box and an increase in depression-like behavior (sucrose preference test) for some days after incision. 86 , 168 Other studies assessing anxiety-like behavior after incision in rats gave similar results by using slightly different approaches and study designs. 36 , 97 Interestingly, the anxiety-like behavior lasted longer than hyperalgesia in 2 (but not one) of these studies.…”
Section: Animal-experimental Basic Researchmentioning
confidence: 89%
“…Systemic administration of gabapentin, or inhibition of ERK within the anterior cingulate cortex (ACC) early after surgery, but not systemic morphine, reduced incision-induced anxiety. 36 , 86 , 97 Interestingly, ERK-inhibition reduced anxiety-like behavior and mechanical hyperalgesia early after surgery (1 hour), but (different to inflammatory and neuropathic pain) in the later phase (6 hour), it exclusively reduced anxiety.…”
Section: Animal-experimental Basic Researchmentioning
confidence: 94%
“…Pain-induced negative sequelae can be more disabling than the pain itself, severely affecting the daily activities of patients with persistent pain [ 5 ]. Many studies on persistent pain have paid considerable attention to its effects on anxiety-like behavior [ 32 , 33 ]. It is necessary to distinguish the sensory and affective changes in pain treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Human studies have shown a positive correlation between DED severity and symptoms of anxiety 7,[60][61][62] . While there have been some reports of increased signs of anxiety in chronic pain models, other reports have not found a significant effect of pain on anxiety measures [63][64][65][66][67][68][69][70] . Using the elevated plus maze, single LGE reduced open arm time only in female mice, whereas double LGE reduced open arm time in both female and male mice.…”
Section: Discussionmentioning
confidence: 93%